A new classification method to simplify blue whale photo-identification technique - Gendron, D.; De La Cruz, A. Ugalde (J. Cetacean Res. Manage., 2023)
Individual identification of blue whales is based on unique pigmentation patterns. Historically photo-identification has been based on the pigmentation patterns observed on a large portion of the animal’s flanks. The new classification method presented here is based primarily on seven dorsal fin shapes and secondarily on five pigmentation patterns selected from a minor portion of the flank adjacent to the dorsal fin. This classification is then applied to a blue whale catalogue that comprises 621 individuals photo-identified in the waters adjacent to the Baja California Peninsula in Mexico. The classification system adequately divides the number of individuals per dorsal fin category and pigmentation patterns. It has been useful not only for reducing time and for matching photographs more efficiently but also has facilitated the finding of intra-catalogue photographic recaptures or photo-recaptures and has enhanced the efficiency of the field work. This new classification method should be considered by other blue whale researchers and for future inter-catalogue comparisons.